Functional analysis of parvin and different modes of IPP-complex assembly at integrin sites during Drosophila development. - Vakaloglou, K.M.; Chountala, M.; Zervas, C.G. (Journal of Cell Science, 2012)
Integrin-linked kinase (ILK), PINCH and parvin constitute the tripartite IPP complex that maintains the integrin-actin link at embryonic muscle attachment sites (MASs) in Drosophila. Here we showed that parvin null mutants in Drosophila exhibit defects in muscle adhesion, similar to ILK and PINCH mutants. Furthermore, the identical muscle phenotype of the triple mutant, which for the first time in any organism removed the entire IPP-complex function, genetically demonstrated that parvin, ILK and PINCH function synergistically. This is consistent with the tight localization of the tripartite complex at sites of integrin adhesion, namely MASs in the developing embryo and focal-contact-like structures in the wing epithelium. Parvin contains tandem unconventional calponin-homology (CH) domains separated by a linker sequence, and a less-well conserved N-terminal region. In vivo structure-function analysis revealed that all the domains are essential for parvin function, whereas recruitment at integrin adhesion sites is mediated by two localization signals: one located within the CH2 domain as previously reported, and a second novel signal within the CH1 domain. Interestingly, this site is masked by the linker region between the two CH domains, suggesting a regulatory mechanism to control parvin localization. Finally, whereas in muscles only ILK controls the stability and localization of both PINCH and parvin, in the wing epithelium the three proteins mutually depend on each other. Thus molecular differences exist in the assembly properties of IPP complex in specific tissues during development, where differential modulation of the integrin connection to the cytoskeleton is required.